Effect of Commitment, Motivation and Feedback to Job Performance - Sulis Rochayatun; Marida Fandi Setiawan (Perkumpulan Praktisi Akuntansi Indonesia, 2020)
This study aims to determine the effect of variable commitment, motivation and feedback on Job Performance at PT BPR ADB and PT. BPR EUJ. Samples to be taken in this study of 100% of the target population. Data were collected using the questionnaire method by providing a list of questions or questionnaires directly to the respondents. Techniques of data analysis in this study using the data validity test with validity and reliability, multiple linear regression analysis, the classical assumption test, F test, t test, analysis of the coefficient of multiple determination and analysis of the partial coefficient of determination. The results showed that BPR. ADB, variable commitment, motivation and feedback simultaneously significant effect on Job Performance variables. The independent variables are: commitment to partially significant effect on Job Performance. Meanwhile, two other independent variables are: the motivation and the feedback effect is not significant to the performance. Commitment is an independent variable that has the most impact on performance. BPR. EUJ, variable commitment, motivation and feedback simultaneously significantly effect on Job Performance variables. The independent variables are motivation partially significant effect on Job Performance. Meanwhile, the two other independent variables are: commitment and the feedback effect is not significant to the performance. Motivation is an independent variable that has the most impact on performance.